(untitled) (International Seven Journal of Health Research, 2024)
Synchronous tumors, characterized by the simultaneous presence of neoplasms in different regions or by confirmatory diagnoses separated by up to six months, are generally associated with unfavorable prognoses, especially in the case of colorectal carcinomas, where they have higher mortality and postoperative complications, as well as requiring a new therapeutic approach and resulting in less favorable clinical outcomes. Colorectal cancer is the most common neoplasm of the gastrointestinal tract, and recent studies indicate that between 15% and 25% of patients with colorectal carcinoma have synchronous tumors, highlighting their clinical relevance and the need for appropriate approaches.